Evaluation of canine dental health problems in Ibadan, Nigeria (2014)
Clinical evaluation for Dental Disease Conditions (DDC) in companion animals is an integral aspect of routine dental health care procedure in veterinary practice which often is less practice in Nigeria. This study evaluated the occurrence of DDC and possible inciting causes with a focus of providing a meaningful basis for canine dental health care in Nigeria. Fifty-seven dogs (30 males and 27 females) made up of 10 different breeds and presented at 3 major Veterinary Hospitals in Ibadan, Nigeria were assessed for periodontal disease (PD), dental calculus (DC), dental abrasion (DA) and their association with other systemic diseases using Dental probe, Glucometer, Urinalysis strip and PD survey questionnaire. Data were analyzed using descriptive statistics and correlation at > 0.05 level of significance. The prevalence of PD was the highest (82.46%) while DC was 80.70% and DA, 57.89%. PD was observed to be more common in male (83.33%) dogs, while calculus formation and dental attrition were more common in female dogs. The incidence and severity of dental disease conditions increased with age. There was a positive correlation (p=0.04) between PD and DC and between DC and DA (p=0.00). The order of nutritional inciting cause of PD, DC and DA is compounded food > home food > waste from eateries. This investigation showed a high incidence of DDC in dogs with no dental health care and nutrition could be an inciting cause. This showed that there is need for patients’ dental health care in veterinary practice in Nigeria